O15 What is the acceptability of online HIV pre-exposure prophylaxis (PrEP) care, drawing on lessons learned from remote PrEP provision during the Covid-19 pandemic? Findings from a qualitative study with gay, bisexual and other men who have sex with men (GBMSM). (16th June 2022) - Kincaid, Ross; Gibbs, Jo; Frankis, Jamie; Dalrymple, Jenny; Estcourt, Claudia
Abstract : Introduction: Online provision of PrEP care could help expand coverage to achieve HIV transmission elimination goals. An online PrEP clinic is being developed in Scotland, consisting of postal self-sampling for STIs and BBVs, an automated online consultation, and remote provision of medication. PrEP users' experiences of telephone-based PrEP care introduced during the Covid pandemic could inform the development of the online PrEP clinic. We explored the acceptability of the online PrEP clinic, drawing on PrEP users' experiences of telephone-based PrEP services. Methods: We conducted semi-structured interviews with 15 GBMSM PrEP users recruited via an urban NHS sexual health service and online cohort (May-December 2021). Glasgow Caledonian University and NHS Scotland granted ethical approval. We used framework thematic analysis to analyse data. Results: Participants felt that telephone-based PrEP care often lacked continuity, was burdensome, and felt impersonal. Despite this, participants felt the quality of care remained high and found the system easy to navigate. Participants found the proposed online PrEP clinic highly acceptable and identified potential benefits (e.g. convenience, privacy, and normalising PrEP) and challenges (e.g. fewer opportunities to ask questions and potentially forgetting to complete the self-sampling kit). Participants felt that SMS reminders, a helpline, and the ability to switch to in-person care when needed would support them to self-manage their PrEP care online. Discussion: The proposed online PrEP clinic was highly acceptable to GBMSM, but integral support features will be needed to optimise its use, including personalisation and integration within existing care pathways to ensure continuity of care.